Exploding a myth "conventional wisdom" or scientific truth? - Dunning-Davies, Jeremy (Horwood, 2007)
Inside front cover flap: Professor Jeremy Dunning-Davies had been sincerely and deeply worried over for a number of years by the pernicious effects that non-scientific influences have had, and continue to have, on scientific research. This book expresses his concern that many scientific theories are not treated as theories, but are being perceived as already proven. Challenges to these 'ideas hypotheses and suppositions' are therefore seldom acknowledged or supported by certain sectors of the establishment. If these outside pressures adversely influence the area of physics, Professor Dunning-Davies put forward the very real possibility of them affecting other areas of science such as medicine, where trust and honesty assume increasing importance.
Keywords: Gesellschaft; Naturwissenschaft; Philosophie; Civilization; Communication in science; Research; Research -- Philosophy; Science; Science and civilization; Science and state; Science in popular culture; Science -- Social aspects; Pseudowissenschaft; Wissenschaftlichkeit; Subjektive Theorie; Wissenschaft